Komponen Keterpaduan Objek Wisata di Kawasan City Walk Slamet Riyadi Ditinjau dari Sistem Pariwisata - Hafiza Jasmine Azzahra; Winny Astuti; Erma Fitria Rini (Regional Development Information Center, Universitas Sebelas Maret, 2018)
Tourism today is an activity that almost everyone in the world does. Each city tries to develop their tourism potential. One concept that can be carried out is city walk tourism. Surakarta city declares itself as a tourism city. In 2007, the Surakarta Municipality revitalized Slamet Riyadi city walk area, which along the road, there are some old buildings and tourist objects that can be visited. The tourism system is a complex thing that consists of several components that are interconnected. The function of the tourism system can be divided into two, from demand side and supply side, which has its own components. With the construction along Slamet Riyadi city walk, which passes several tourist objects, this momentum can be utilized to improve the tourism sector in Surakarta. In order to run optimally, it is necessary to see what the components of tourism system that required are. The method used in this research is literature review and crossing variables. These methods were used to find out what variables are important in the tourism system at Slamet Riyadi city walk. Of these two methods the output will be the integrated tourism components that influenced in tourist attraction at Slamet Riyadi city walk.